The role of sex, attachment and autonomy‐connectedness in personality functioning. (27th August 2015) - Bachrach, Nathan; Croon, Marcel A.; Bekker, Marrie H. J.
Abstract Previous studies have found significant relationships among sex, attachment and autonomy‐connectedness and DSM‐IV personality characteristics. In the present study, we aimed to add to the current knowledge about attachment‐related aspects of personality pathology, by examining the relationships of these same variables with dimensions of pathological personality structure as conceptualized by Kernberg. The study was performed among 106 ambulatory patients from a Dutch mental healthcare institute. A path model based upon neo‐analytical object relation theory and attachment theory was tested. We expected significant associations among sex, attachment, autonomy and aspects of personality functioning. Both insecure attachment styles as well as the autonomy‐connectedness components of sensitivity to others (SO) and capacity of managing new situations predicted general personality dysfunctioning significantly. More specifically, reality testing was negatively predicted by the autonomy component of capacity of managing new situations, and aggression was significantly predicted by sex as well as both insecure attachment styles. We advise scientists as well as clinicians to be alert on sex differences in autonomy‐connectedness and aspects of personality dysfunctioning. Taking sex‐specific variations in attachment and autonomy into account next to a more explicit focus on insecure attachment styles and autonomy problems may enhance, the current relatively low, treatment effectiveness for personality pathology. Copyright © 2015 John Wiley & Sons, Ltd.